Towards sustainable liveihoods: trends and survival strategies used in street vending in Masvingo, Zimbabwe - Matenga, Luckymore (My University, 2018)
The deepening economic crisis, coupled with increasing rates of poverty and unemployment, has led to the proliferation of street vending in Zimbabwe. Moreover, the dilemma of inconsistency in socio-economic policy has thrown the generality of the working class into vicious cycles of deprivation thereby compounding growth of informality. Clash of interests between the central and local government on the regulation of the informal sector has compounded the plight of street vendors; especially as the formulation of favourable policies remains an unaccomplished. Qualitative methodology was employed where a mini focus group discussion, observation method; key informants and unstructured interviews were used to solicit data while participants were purposively selected. This study unearths the survival strategies used by street vendors to sustain their livelihoods in Masvingo, Zimbabwe. The research was carried out in the City of Masvingo located in the Southern region of Zimbabwe. The research proposes an in-depth understanding of street vendors’ perception on policies used to govern them and the challenges they face. It establishes that street vending has played an important role in employing many urbanites in Zimbabwe against the backdrop of massive crackdowns by city officials. It argues that the failure of the government to integrate street vending into the mainstream economy impinges on proper urban planning and the attainment of Sustainable Development Goals (SDGs).
Keywords: Small business--Zimbabwe; Street vendors--Zimbabwe